The transducin cascade is involved in the light-induced structural changes observed by neutron diffraction on retinal rod outer segments. - Vuong, T M (1987)
Time-resolved neutron diffraction on retinal rod outer segments are performed to reinvestigate the origin of the light-induced structural change observed by Saibil et al. (Saibil, H., M. Chabre, and D. L. Worcester, 1976, Nature (Lond.), 262:266-270). Photoactivating rhodopsin triggers in rods a cascade of GTP-dependent and transducin-mediated reactions controlling cyclic-GMP hydrolysis. Infrared light-scattering studies (Kühn, H., N. Bennett, M. Michel-Villaz, and M. Chabre, 1981, Proc. Natl. Acad. Sci. USA, 78:6873-6877; Vuong, T. M., M. Chabre, and L. Stryer, 1984, Nature (Lond.), 311:659-661) demonstrated the existence of structural changes that correspond to this cascade rather than to rhodopsin photoactivation. We thus look for neutron diffraction changes of similar origins. With 1-min time resolution, intensity changes are observed mainly for orders 2 and 4. The illumination and GTP dependence of these changes indicates an involvement of transducin. Without GTP, they are linear with the amount of photoexcited rhodopsin, saturate at 10% photolysis, and thus correlate well with the light-scattering "binding signal." With GTP, light sensitivity is higher and saturation occurs below 0.5% photolysis, as for the "dissociation signal" of light scattering. In both cases, lattice compressions of 0.2-0.3% are observed. With 4-s time resolution the intensity change with GTP present precedes the lattice compression. The fast intensity change is probably due to the displacement of transducin alpha-subunits away from the disc membrane and the slower lattice shrinkage to an osmotic readjustment of the rod.